Persuading Effect of Store Aesthetics on Shoppers' Purchase Intentions: The Gender Difference - Mishra, Pallabi (Indian Journal of Marketing, 2014)
The spending capacity and willingness of customers has increased in India. Keeping this in mind, marketers have come up with organized retail outlets to attract and cater to the customers' needs. A well-designed and finely maintained store not only attracts more footfalls, but also increases the sales. Apart from that, beautification, which is known as aesthetics of the store, is also important for the marketers. Gender differences have been found to play a major role in buying behaviour. This paper focused on studying the most preferred aesthetic element of the store (both exterior and interior) by both the genders. Furthermore, the effect of these elements on the purchase intentions of the customers was also analyzed by regression. The study was conducted at a leading apparel store in the city of Cuttack, Odisha. The results showed that product display was the most preferred factor by both genders, having the maximum effect on their purchase intentions. A major difference was found in the preference of both genders with respect to the external appearance of the store and music played in the store. This research will help managers to understand the preferences of the customers in a store and design the store aesthetically to attract more footfalls and generate purchases.